2013
DOI: 10.3389/fpsyg.2013.00645
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced musical rhythmic perception in Turkish early and late learners of German

Abstract: As language rhythm relies partly on general acoustic properties, such as intensity and duration, mastering two languages with distinct rhythmic properties (i.e., stress position) may enhance musical rhythm perception. We investigated whether competence in a second language (L2) with different rhythmic properties than a L1 affects musical rhythm aptitude. Turkish early (TELG) and late learners (TLLG) of German were compared to German late L2 learners of English (GLE) regarding their musical rhythmic aptitude. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 87 publications
4
18
0
Order By: Relevance
“…Effects are small, but they are particularly impressive given that scores on MET subtests are highly correlated. Results also replicate those of W allentin et al (2010), who showed significant effects o f musical experience on MET scores, as well as those o f Marie et al (2012) and Roncaglia-Denissen et al (2013), who showed stronger links be tween linguistic experience and rhythm perception than between linguistic experience and pitch/melody perception.…”
Section: Discussionsupporting
confidence: 87%
“…Effects are small, but they are particularly impressive given that scores on MET subtests are highly correlated. Results also replicate those of W allentin et al (2010), who showed significant effects o f musical experience on MET scores, as well as those o f Marie et al (2012) and Roncaglia-Denissen et al (2013), who showed stronger links be tween linguistic experience and rhythm perception than between linguistic experience and pitch/melody perception.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, melodic perception would not have overlapped as strongly with the rhythmic grouping task, resulting in a weaker association between the two. This result is also in line with those of previous studies: There is evidence that speech rhythm experience and musical rhythm discrimination abilities are linked (Roncaglia-Denissen et al, 2016;Roncaglia-Denissen et al, 2013a), and experience with lexical tone has been linked with receptive skills for musical melody (Bidelman et al, 2013;Deutsch et al, 2006;Wong et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…A few studies have addressed crosscultural differences in listening preferences (Soley & Hannon, 2010) and perceptual tasks (Hannon, Soley, & Ullal, 2012; Roncaglia-Denissen, Schmidt-Kassow, Heine, Vuust, & Kotz, 2013), showing that familiarity and enculturation governs listeners' rhythmic and metrical frameworks. However, whether syncopations have similar or different perceptual effects and whether meter relies on similar or different mechanisms within other musical styles is unexplored.…”
Section: Espite Widespread Advances In Under-mentioning
confidence: 99%